Entrepreneurial Leadership Challenges in a Project-Based Wellness Business: A Qualitative Case Study of Yogashala’s Organizational Development - Fazira Rizqy Alfitri; Aditya Liliyan; Agata Safira Prahmayuda (Research Synergy Foundation, 2026)
This study examines the application of entrepreneurial leadership in the context of organizational development at the Yogashala wellness business. It is motivated by the phenomenon of young-generation leadership, which tends to be adaptive and innovative but often faces challenges in terms of planning and organizational coordination. A qualitative approach using a case study design was employed to gain an in-depth and contextual understanding of these leadership dynamics. Data were collected through interviews, direct observation, and document analysis involving the business owner of Yogashala. The research findings reveal that entrepreneurial leadership at Yogashala is reflected in the leaders’ ability to design innovative programs, identify market opportunities, and develop wellness concepts responsive to community needs. A flexible and collaborative leadership style has proven effective in fostering active team member participation. However, the tendency to prioritize innovation and speed of execution has not been balanced with systematic planning, leading to issues such as internal miscommunication, ineffective coordination, and operational obstacles. The study concludes that organizational sustainability requires balancing the flexibility of entrepreneurial leadership with the strengthening of transformational leadership to ensure a more structured and sustainable direction for business development.